TANTANGAN DAN DAMPAK INTEGRASI EKONOMI REGIONAL TERHADAP PEMBANGUNAN EKONOMI KAWASAN ASEAN - Hamzah Miftahun Ni’am; Nisrina Hasna Salsabila; Umu Latifah; Sarpini Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Regional economic integration is becoming an increasingly important phenomenon in the development of the international economic system, including the ASEAN region. The purpose of this article is to explain the challenges and impacts of regional economic integration on ASEAN's economic development. Through a qualitative approach using literature review techniques, this article identifies factors that influence the process of economic integration, such as global economic growth, population problems, urbanization rates, and resource scarcity. Economic integration offers opportunities to encourage trade, investment and economic growth, but also brings challenges such as development gaps and threats to local industries. To face these challenges, close cooperation among ASEAN member countries is essential to create sustainable economic stability.